Duvertepe Kaolin Deposits in Balikesir (North-west Turkey) and Ceramic Properties - Mahmut Kilic, Ahmet; Kilic, Ozen; Ekrem Aritan, A. (Asian Journal of Chemistry, 2010)
The Duvertepe kaolin deposits (Caltilitaban and Bagkiran) were characterized and assessed potentially in the ceramic industry. The particle size, colour measurement, viscosity, plastic limits, liquid limits, firing shrinkage, water absorption, water-soluble matter and moisture were tested by chemical, physico-mechanical, mineralogical and the thermal analysis techniques (TG-DTA) and their firing behaviours were investigated. The technological properties of Duvertepe kaolins were determined concerning shrinkage, firing and colour. From these studies, it was understood that the Duvertepe kaolin could be used for ceramic industry, fabrication of tiles, bricks and sanitary wares.